2010
DOI: 10.1590/s1517-83822010000100032
|View full text |Cite
|
Sign up to set email alerts
|

2(5H)-Furanone: a prospective strategy for biofouling-control in membrane biofilm bacteria by quorum sensing inhibition

Abstract: Biofouling of membranes demands costly periodic cleaning and membrane replacement. A sustainable and environmentally friendly solution for maintenance is not available and would be of great interest for many purposes including economical. As complex biofilm formation by environmental strains is the major cause of biofouling and biofilm formation in most cases are controlled by N-Acylhomoserine lactone (AHL)-mediated Quorum Sensing (QS). An effort was made to understand the appropriateness of 2(5H)-furanone, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Due to the clinical, environmental and industrial application of the QS inhibitors, search for potential compounds with anti-QS activity has increased over the last few years [25] . Efforts towards the development of anti-QS compounds should provide a means of treating bacterial infections without the overuse of antibiotics that unavoidably develop resistant organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the clinical, environmental and industrial application of the QS inhibitors, search for potential compounds with anti-QS activity has increased over the last few years [25] . Efforts towards the development of anti-QS compounds should provide a means of treating bacterial infections without the overuse of antibiotics that unavoidably develop resistant organisms.…”
Section: Discussionmentioning
confidence: 99%
“…These microorganisms were actively involved in biofilm formation on membranes, suggesting that biochemical control of biofilm formation by inhibiting QS signals could be an effective way to reduce membrane biofouling. Ponnusamy et al [147] found that 2(5-H) furanone can be used for suppressing biofilm formation by environmental strains of bacteria, such as Aeromonas hydrophila , isolated from a bio-fouled RO membrane system. Kappachery et al [148] demonstrated that a commercially available vanillin (4-hydroxy-3-methoxybenzaldehyde) can be used to prevent the establishment of biofilm on RO membrane surfaces.…”
Section: Biofouling Prevention and Controlmentioning
confidence: 99%
“…Recently, 2(5-H) furanones (non-halogenated), a commercially available compound, was found to block the production of AHL signalling molecules, and it significantly reduced biofilm formation on a fouled RO membrane. 2(5-H) furanones are believed to act as a potential quorum inhibition agent in a bacterial biofilm community [37]. However, furanone compounds are considered to be toxic and chemically unstable and therefore, these compounds are not suitable for water purification systems [37] Some natural products from different plant sources have also been used to control membrane biofouling based on quorum sensing.…”
Section: Blockage Of Signal Productionmentioning
confidence: 99%
“…2(5-H) furanones are believed to act as a potential quorum inhibition agent in a bacterial biofilm community [37]. However, furanone compounds are considered to be toxic and chemically unstable and therefore, these compounds are not suitable for water purification systems [37] Some natural products from different plant sources have also been used to control membrane biofouling based on quorum sensing. A study by Ponnusamy et al [19] revealed that exposure of A. hydrophila biofilms to vanillin (from vanilla beans) resulted in reduced production of AHL molecules and decreased biofilm formation on a reverse osmosis membrane.…”
Section: Blockage Of Signal Productionmentioning
confidence: 99%